1998
DOI: 10.1128/aac.42.2.269
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Simultaneous Detection of Phenotypic Resistance to Inhibitors of Protease and Reverse Transcriptase in Recombinant Human Immunodeficiency Virus Type 1 Isolates from Patients Treated with Antiretroviral Drugs

Abstract: Combination therapy with protease (PR) and reverse transcriptase (RT) inhibitors can efficiently suppress human immunodeficiency virus (HIV) replication, but the emergence of drug-resistant variants correlates strongly with therapeutic failure. Here we describe a new method for high-throughput analysis of clinical samples that permits the simultaneous detection of HIV type 1 (HIV-1) phenotypic resistance to both RT and PR inhibitors by means of recombinant virus assay technology. HIV-1 RNA is extracted from pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(111 citation statements)
references
References 40 publications
3
107
0
1
Order By: Relevance
“…Of these, Virco's (Virco, Mechelen, Belgium) virco Ò TYPE HIV-1 (vT) and Antivirogram Ò (AVG), and Monogram Biosciences' (Monogram Biosciences, Inc., South San Francisco, CA) PhenoSenseÔ (PS) assays are used most widely. AVG and PS are conventional phenotypic assays measuring fold-changes in IC 50 (FC) in vitro, while vT provides calculated fold-changes in IC 50 from a viral genotype using the VirtualPhenotypeÔ-LM (VPT-LM) bioinformatics tool and a large database of viral isolates for which genotypic and phenotypic information is available and correlated [Hertogs et al, 1998;Petropoulos et al, 2000;Vermeiren et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, Virco's (Virco, Mechelen, Belgium) virco Ò TYPE HIV-1 (vT) and Antivirogram Ò (AVG), and Monogram Biosciences' (Monogram Biosciences, Inc., South San Francisco, CA) PhenoSenseÔ (PS) assays are used most widely. AVG and PS are conventional phenotypic assays measuring fold-changes in IC 50 (FC) in vitro, while vT provides calculated fold-changes in IC 50 from a viral genotype using the VirtualPhenotypeÔ-LM (VPT-LM) bioinformatics tool and a large database of viral isolates for which genotypic and phenotypic information is available and correlated [Hertogs et al, 1998;Petropoulos et al, 2000;Vermeiren et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on the development of recombinant virus assays, based on direct amplification of patient-derived sequences from plasma. Different systems in which recombinant viruses are generated by either homologous recombination [Hertogs et al, 1998] or direct cloning [Petropoulos et al, 2000;Klimkait, 2002] have demonstrated important advantages for large-scale applications. In addition to be fast and reproducible methods, shorter culture times minimize the outgrowth of minor variants in comparison with conventional phenotypic assays.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic changes were reported at codons associated with phenotypic resistance to NRTIs and NNRTIs. Phenotypic resistance assays to ddI, ddC, d4T, ZDV, 3TC and ABC were carried out by Virco NV, Belgium, using the recombinant virus assay [8]. Phenotype was expressed as fold resistance increase over wild-type (the ratio of wild-type to patients' variant IC 50 values).…”
Section: Baseline Genotypic and Phenotypic Analysesmentioning
confidence: 99%